Avaliação experimental do desempenho mecânico de cavilhas de madeira engenheirada - Camargo, Marcos Vinício de (2023)
The civil construction industry in the world context has sought more efficient construction systems with regard to environmental preservation. The wood usually used comes from native forests, which are increasingly scarce. With the strengthening of sustainability concepts, the need to develop viable alternatives for the rational use of species from planted forests was created. In this context, the present work presents the use of wood from the Pinus taeda species in order to add value to this raw material with great availability in the market. The research presents the characterization process of Pinus taeda and Eucalyptus saligna woods, as well as the behavior of Pinus wood after being subjected to the impregnation process with methyl methacrylate monomer (MMA) impregnation method by vacuum - pressure, and thus increase the average values of the mechanical properties of wood from the species Pinus taeda. Proposing the use of engineered wood of the Pinus taeda species in the manufacture of dowels with the purpose of replacing metallic in wooden connections. To achieve this objective, an experimental program was carried out to characterize Pinus taeda and Eucalyptus saligna woods, followed by impregnation tests and finally the elaboration and characterization of engineered dowels with (MMA). After carrying out the experimental program, satisfactory results were found, where the impregnation method proved to be effective, showing a gain in resistance to compression parallel to the fibers fc0 of Pinus taeda wood, denoting gains of up to 92% when compared to pieces without impregnation. Where the analyzes in dowels also showed stiffness gains for their use in connection elements